The mediating role of technostress in the relationship between social outcome expectations and teacher satisfaction: evidence from the COVID-19 pandemic in music education - Ferdinando Toscano; Teresa Galanti; Veronica Giffi; Teresa Di Fiore; Michela Cortini; Stefania Fantinelli (Association for Learning Technology, 2024)
The COVID-19 pandemic has prompted significant changes in education, including a widespread transition from traditional, in-person instruction to online learning, which has also affected music conservatories. This study investigates the relationship between social outcome expectations and teacher satisfaction with remote education (SRE) among conservatory music professors during the pandemic. Rooted in the Social Cognitive Theory (SCT), the study examines whether technostress mediates this relationship and whether the intention to use information and communication technology (ICT) moderates it. A cross-sectional survey was conducted among 108 Italian conservatory teachers through an online self-report questionnaire. The results indicate a negative indirect effect of social outcome expectations on teacher satisfaction through technostress. However, surprisingly, the direct effect was positive and stronger. The study suggests that social expectations lead to technostress. Still, they also present an opportunity for music educators to embrace the challenge of remote education and increase their satisfaction with it.